„Pan sądzi, że koniec bliski?”. Późny modernizm, duchy kina i Wesele Andrzeja Wajdy - Stelmach, Miłosz (Przestrzenie Teorii, 2017)
The aim of the article is to place Andrzej Wajda’s work from the early 1970s in the late-moderist trend developing in Polish film at that time. The best example of this is The Wedding (1972), which implements modernist strategies of subjectification, self-reflection and stylisation at the artistic and narrative level. The presence of ghosts in this film especially leads to a theoretical discussion on the spectral nature of the medium of film.